2019
DOI: 10.1016/j.ypmed.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for alcohol use among pregnant women, ages 15–44, in the United States, 2002 to 2017

Abstract: Fetal alcohol exposure can lead to severe birth and developmental defects. Determining which pregnant women are most likely to drink is essential for targeting interventions. In National Survey on Drug Use and Health data on pregnant women from 2002-2017 (N=13,488), logistic regression was used to produce adjusted odds ratios (aOR) indicating characteristics associated with two past-month outcomes: any alcohol use and binge drinking. Risk factors were sociodemographic (age, race/ethnicity, marital status, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The U.S. National Survey on Drug Use and Health survey reported on risk factors for alcohol use among 13,488 pregnant women, aged 15 to 44, in the United States from 2002 to 2014 (Shmulewitz and Hasin, ). Higher risk for any drinking and binge drinking was observed among pregnant women with other substance use including tobacco (aORs 2.9 to 25.9), depression (aOR 1.6), and unmarried status (aORs 1.6 to 3.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The U.S. National Survey on Drug Use and Health survey reported on risk factors for alcohol use among 13,488 pregnant women, aged 15 to 44, in the United States from 2002 to 2014 (Shmulewitz and Hasin, ). Higher risk for any drinking and binge drinking was observed among pregnant women with other substance use including tobacco (aORs 2.9 to 25.9), depression (aOR 1.6), and unmarried status (aORs 1.6 to 3.2).…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk for any drinking was observed in those with higher education and income. However, higher risk was observed for binge drinking in the second and third trimesters among Blacks (aOR 3.3) and those with lower income and less education (Shmulewitz and Hasin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher education was also associated with alcohol cessation between early and middle pregnancy, and therefore education was not associated with alcohol use in middle pregnancy. There is some evidence that highly educated women were more likely to consume alcohol before becoming aware of their pregnancy, and more likely to continue or reduce rather than cease alcohol use during pregnancy in Western countries [12,14,[16][17][18]. Meanwhile, two studies in Japan showed that highly educated women were more likely to cease alcohol use after becoming aware of their pregnancy [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in prevalence of alcohol use have been reported between early pregnancy and middle/late pregnancy [8][9][10][11][12]. Although this suggests that predictors of alcohol use may differ by pregnancy stage, very few studies have been conducted at different points during pregnancy [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…First, maternal perinatal mental disorders have a wide spectrum of independent adverse effects on the developing fetus (Stein et al 2014;Waters et al 2014). Second, prenatal stress and depression have been found to predict unfavorable health practices (Alhusen et al 2016;Cannella et al 2018) and a higher risk of substance use in pregnancy (Alhusen et al 2016;Hyer et al 2019;Shmulewitz and Hasin 2019). Generally, stress associates with increased craving, and potentially with opioid use, among persons with an opioid use disorder (MacLean et al 2019).…”
mentioning
confidence: 99%